2004
DOI: 10.1074/jbc.m405253200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced Conformational Shift in the N-terminal Domain of GRP94, an Hsp90 Chaperone

Abstract: The hsp90 1 family of molecular chaperones is required for the activation of a large number of proteins, including those involved in eukaryotic cell cycle regulation, signal transduction, immune response, and transcription (1, 2). GRP94 (also known as gp96), the endoplasmic reticulum paralog of cytoplasmic Hsp90, participates in the maturation of proteins that are transported to the cell surface, including Toll-like receptors and certain integrins (3), or secreted, such as IgGs (4, 5). The activity of the hsp9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 47 publications
9
129
0
Order By: Relevance
“…Indeed, the subsequent crystal structures of the ATP-bound full-length dimer have revealed a major conformational change, involving swapping of the N-terminal chain and lid refolding on the ATP-binding site. The comparison of our modeled Hsp90 NTD structures with the crystal structures of GRP94, the ER paralog of Hsp90, in the complex with ATP (PDB entry 1TC0) (25), the apo form (PDB entry 2YT2) (37), and the structure of yeast Hsp90 (PDB entry 1AH6) (38) has confirmed that in the isolated N-domain the lid is in the open conformation. The inhibitor bound complexes were obtained starting from the complex of human Hsp90 in complex with geldanamycin (PDB entry 1YET) (16), removing the inhibitor and docking Shepherdin, Shepherdin[79 -83] or AICAR as described in refs.…”
Section: Molecular Dynamics Of Hsp90mentioning
confidence: 56%
See 2 more Smart Citations
“…Indeed, the subsequent crystal structures of the ATP-bound full-length dimer have revealed a major conformational change, involving swapping of the N-terminal chain and lid refolding on the ATP-binding site. The comparison of our modeled Hsp90 NTD structures with the crystal structures of GRP94, the ER paralog of Hsp90, in the complex with ATP (PDB entry 1TC0) (25), the apo form (PDB entry 2YT2) (37), and the structure of yeast Hsp90 (PDB entry 1AH6) (38) has confirmed that in the isolated N-domain the lid is in the open conformation. The inhibitor bound complexes were obtained starting from the complex of human Hsp90 in complex with geldanamycin (PDB entry 1YET) (16), removing the inhibitor and docking Shepherdin, Shepherdin[79 -83] or AICAR as described in refs.…”
Section: Molecular Dynamics Of Hsp90mentioning
confidence: 56%
“…It is worth noting that ATP-induced conformational changes have been also observed in GRP94, the endoplasmatic reticulum paralog of Hsp90 (25). In this case, ATP binding was shown to induce dramatic conformational rearrangements in the helices 1, 4, and 5 (corresponding to the N-terminal helix and the ATP-lid), which in turn resulted in the assembly of a second NTD in a functional dimer (25). In contrast, we have found that deletion of the terminal phosphate group in the ADP complex and binding with the inhibitors can minimize repulsive interactions ( Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The endoplasmic reticulum homolog, Grp94, has a unique 5 amino acid insertion in the lid (residues 182-186) leading to a structural rearrangement of the lid in response to nucleotide that is different from other Hsp90 homologs ( Figure 4C). Although the lid position is unique in nucleotide-bound Grp94, this conformation also leads to the exposure of a large predominantly non-polar surface (Immormino et al, 2004) as seen in AMPPNPbound yHsp90. The hydrophobic surface may also serve as an interaction site for NTD dimerization in Grp94.…”
Section: Local Structural Changes In the Ntd Due To Nucleotide Bindingmentioning
confidence: 99%
“…The various crystal structures of GRP94 and Hsp90 do not ascribe a clear function to the N-terminal ␤ sheet. For example, there is no obvious conformational change in the ␤ sheet when apo-GRP94 and nucleotide-bound GRP94 are compared (16,25,39). Yet, indirect biophysical evidence suggests that the ␤ sheet binding site is regulated by both the nucleotide-binding site in the N-terminal domain and by the charged domain that links the N and the M domains (3,7).…”
mentioning
confidence: 99%